The Influence of Perceived Social Media Marketing Elements on Consumer–Brand Engagement and Brand Knowledge: A Conceptual Paper - Aprilia Diahayu Ningtias; Arry Widodo; Nurafni Rubiyanti; Anita Silvianita (International Journal of Scientific Multidisciplinary Research, 2024)
With the development of information technology, people's lifestyles, especially in Indonesia, have changed. Now the use of social media is not only used for communication tools, even marketing on social media has become a trend today. This trend has triggered local brands to continue expanding and building customers by conducting marketing activities on social media. Aside from Indonesia's changing consumer behavior, there is an increase in young entrepreneurs in Indonesia. The beauty industry is one of the fastest growing industries in many countries. Sales of personal care products and cosmetics have experienced significant growth in recent years. This study aims to determine how much customer response regarding social media marketing, consumer brand engagement and brand knowledge on The Originote brand. Marketing is very diverse, starting from social media content that is designed as attractive as possible to attract consumer buying interest